Osteoid Osteoma of the Intercondylar Notch: An Uncommon Cause of Knee Stiffness - Frank, Rachel M.; Chalmers, Peter Nissen; Cole, Brian J.; Gitelis, Steven (The Journal of Knee Surgery Reports, 2015)
The presence of an osteoid osteoma in a periarticular or intra-articular location about the knee is rare. Osteoid osteoma of the knee may be present with nonspecific complaints including knee pain, stiffness, effusions, and atrophy. Depending on the clinical setting, these symptoms could represent a variety of different diagnoses, including meniscal pathology, chondral pathology, synovitis, or Plica syndrome. In this article, we present the unique case of an osteoid osteoma within the intercondylar notch of the knee that underwent a significant delay in diagnosis and several unnecessary procedures due to misdiagnosis. Although intra-articular osteoid osteomas have been described, there remains a paucity of case reports discussing these lesions within and around the knee, and currently there are no reports available describing such a lesion located within the intercondylar notch. Although osteoid osteomas are relatively common, the intra-articular location of such lesions presents a diagnostic challenge. Vague, nonspecific symptoms including joint pain, swelling, and mechanical symptoms coupled with nonspecific radiographic findings in an otherwise healthy, young patient are more likely to guide the clinician toward a more common diagnosis of a sports-related injury as opposed to a benign bone tumor. This case represents an extremely rare presentation of osteoid osteoma within the intercondylar notch of the knee. The case presentation provides an excellent reminder of the need to consider rare diagnoses such as osteoid osteoma, especially in cases of chronic, unrelenting, localized pain in the absence of any other explicable pathology.
Keywords: intercondylar notch; osteoid osteoma; stiffness; arthroscopy